2019
DOI: 10.3389/fendo.2019.00608
|View full text |Cite
|
Sign up to set email alerts
|

Hexane Fraction of Turbo brunneus Inhibits Intermediates of RANK-RANKL Signaling Pathway and Prevent Ovariectomy Induced Bone Loss

Abstract: Osteoporosis is a “silent disease” characterized by fragile and impaired bone quality. Bone fracture results in increased mortality and poor quality of life in aged people particularly in postmenopausal women. Bone is maintained through the delicate balance between osteoclast-mediated bone resorption and osteoblast-mediated bone formation. The imbalance is caused most often by overly active osteoclasts due to estrogen deficiency. Natural products have long been used to prevent and treat osteoporosis since they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Furthermore, endogenous estrogen production was ceased by ovariectomy, which manifested as marked uterine atrophy in the OVX group, which indicated that OVX worked successfully as a model of estrogen withdrawal. Similar findings were also reported by other investigators [Tsuji et al, 2009; Chaugule et al, 2019]. However, in the present study, exposure to three different PEMF frequencies showed that uterine mass was not affected in OVX mice, which indicates that PEMF can inhibit bone loss without affecting the uterus in OVX mice.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, endogenous estrogen production was ceased by ovariectomy, which manifested as marked uterine atrophy in the OVX group, which indicated that OVX worked successfully as a model of estrogen withdrawal. Similar findings were also reported by other investigators [Tsuji et al, 2009; Chaugule et al, 2019]. However, in the present study, exposure to three different PEMF frequencies showed that uterine mass was not affected in OVX mice, which indicates that PEMF can inhibit bone loss without affecting the uterus in OVX mice.…”
Section: Discussionsupporting
confidence: 92%
“…Later, the cells were stained with Alexa Fluor ® 488 Phalloidin (Cell Signaling Technology, Danvers, MA, USA) in the dark for 15 min at 25 °C. Then, the cells were washed and stained with nuclear 4′,6-diamidino-2-phenylindole dye (Cell Signaling Technology) in the dark for 5 min at 25 °C [ 35 ]. Images were visualized with a light microscope (DMi8; Leica Microsystems).…”
Section: Methodsmentioning
confidence: 99%
“…The current understanding of natural products indicates that they constitute a possible source of potential bone protective agents. Multiple biological and pharmacological in vitro and experimental studies have revealed that a variety of natural products could maintain or promote bone health with potentially beneficial effects and reduced side effects (Chaugule et al, 2019). BA from birch (B. pubescens) and a variety of plants, as a natural pentacyclic triterpene compound, has anti-human immunodeficiency virus (HIV), antibacterial, anti-inflammatory, antimalarial and anti-herpes simplex virus 1 (HSV-1) properties (Amiri et al, 2019).…”
Section: Discussionmentioning
confidence: 99%